ANALISIS MOTIVASI BELAJAR SISWA KELAS VII SMP N 11 PEKALONGAN MENGGUNAKAN APLIKASI MOBILE LEARNING BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN JARAK JAUH - Muhammad Choirul Kamal; Evi Sugiana Purnamasari (Delta: Jurnal Ilmiah Pendidikan Matematika, 2021)
This paper aims to know the learning motivation of android-based mobile learning application usage as a medium of long distance learning (PJJ) for grade VII students SMPN 11 Pekalongan. This paper is implemented at SMPN 11 Pekalongan in grade VII E, VII F, and VII G students through whatsapp and google classroom. The method used in this paper is qualitative method which is descriptive analysis. The data collection is used open and closed questionnaires and interviews to students of grade VII E, VII, F, VII G SMPN 11 Pekalongan.  Based on the questionnaires and the interviews conducted by researcher, it shows 86.5% of students have high learning motivation in PJJ, and the usage of android-based mobile learning applications also can be an alternative for students to study and to understand the learning materials well.